1999
DOI: 10.1029/1998jc900101
|View full text |Cite
|
Sign up to set email alerts
|

Response of the West Florida Shelf circulation to climatological wind stress forcing

Abstract: Abstract. The response of the west Florida continental shelf circulation to monthly mean climatological wind forcing is investigated by using the three-dimensional, primitive equation Princeton Ocean Model. Two basic seasonal patterns of circulation and sea surface elevation occur under a barotropic setting: a winter pattern from October to March and a summer pattern from April to September. An interesting finding in winter is an anticyclonic gyre over the northeastern (Florida Big Bend) region that merges wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 19 publications
6
26
0
Order By: Relevance
“…7C,D , respectively. This result is consistent with the winds reported for the SWF shelf in summer (Yang & Weisberg 1999). On July 4 the alongshore wind stress intensified and changed direction for a few hours, but with no effect on surface currents or water temperature (Fig.…”
Section: Marquesas Station (Mq) -Internal Tidessupporting
confidence: 83%
See 1 more Smart Citation
“…7C,D , respectively. This result is consistent with the winds reported for the SWF shelf in summer (Yang & Weisberg 1999). On July 4 the alongshore wind stress intensified and changed direction for a few hours, but with no effect on surface currents or water temperature (Fig.…”
Section: Marquesas Station (Mq) -Internal Tidessupporting
confidence: 83%
“…Coldwater anomalies often occur as a result of upwelling favorable winds (Weisberg et al 1996), cyclonic gyre circulation (Lee et al 2002), internal tides (Baines 1986) or internal bores (Leichter et al 1996). Winds during the sampling period were weak and mainly from the eastsoutheast, which did not favor coastal upwelling, and were consistent with the winds reported for the SWF shelf in summer (Yang & Weisberg 1999). Cyclonic gyres are common features formed southwest of the Dry Tortugas (Lee et al 1994), which can propagate downstream as transient coastal eddies along the edge of the Florida Keys shelf (Fratantoni et al 1998).…”
Section: Internal Tidessupporting
confidence: 68%
“…The T and S are held unchanged during the integration period. When the wind forcing is applied, the velocity field will respond and results in establishing a combined Ekman and geostrophic balance (Blumberg and Mellor 1983;Yang and Weisberg 1999). The model in the diagnostic mode is initially integrated for 25 days until the kinetic energy of the system achieves nearly a steady state .…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…For this, the Princeton Ocean Model (POM) is implemented for the west coast of India. The POM is earlier used to study different coastal regions including the west Florida continental shelf circulation (Yang and Weisberg 1999), upwelling off the northern California continental shelf (Gan and Allen 2002), and winter and pre-monsoon surface cooling near the Indian southern tip region (Luis and Kawamura 2002a, b). …”
Section: Introductionmentioning
confidence: 99%
“…For example, a seasonal midshelf cold tongue develops in spring as baroclinic pressure gradients are induced in response to temperature gradients formed by differential along and across shelf heating (Weisberg et al 1996;He and Weisberg 2002). Model studies have demonstrated a climatological wind-driven preference for wintertime upwelling and summertime downwelling in the northeastern shelf (Yang and Weisberg 1999). A review of the distribution of our instrumentation over the WFS shows that our IMET/ASIMET sensors are situated closest to the coast and farthest north, while the Weatherpak sensors are farther offshore and south.…”
Section: Air-sea Regime Differencesmentioning
confidence: 99%